2014
DOI: 10.1177/0017896914552203
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of diabetes online patient education materials from academic institutions

Abstract: Objective: The purpose of this study was to assess and compare the readability of type 2 diabetes online patient education materials from academic institutions in the northeast USA and the American Diabetes Association. Many US residents utilise the Internet to obtain health information. Studies have shown that online patient education materials are often written above the recommended fifth grade reading level, and this may pertain to diabetes health information as well. As diabetes is the seventh leading caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Our study found that PEM from professional organizations and an academic institution typically exceeded a 6th-grade reading level. This is in keeping with a previous study, which found that PEM on diabetes mellitus from US academic institutions and professional organizations were written for a reading level of above grade 10 [ 32 ].…”
Section: Discussionsupporting
confidence: 90%
“…Our study found that PEM from professional organizations and an academic institution typically exceeded a 6th-grade reading level. This is in keeping with a previous study, which found that PEM on diabetes mellitus from US academic institutions and professional organizations were written for a reading level of above grade 10 [ 32 ].…”
Section: Discussionsupporting
confidence: 90%
“…It is not uncommon for patient education materials to contain medical terms and medications that are polysyllabic, with no shorter equivalent replacement words available, making their use difficult to avoid (Dorcely et al, 2014). After the booklets in this study were revised, the post-evaluation revealed a majority of content had met or demonstrated improvement for literacy standards including readability, grade level (fifth to sixth grade or 10- to 12-year-olds), understandability and actionability.…”
Section: Discussionmentioning
confidence: 99%
“…The literacy tools used to assess the patient education materials for reading grade level, reading ease, understandability and actionability did not assess for accuracy or comprehensiveness of the content. The use of polysyllabic words is frequently unavoidable (Dorcely et al, 2014). In addition, material that may score well when evaluated by the varying literacy tools does not necessarily translate to the material being effective for the target audience.…”
Section: Discussionmentioning
confidence: 99%
“…Move: select one or more entries to move, click on the "move" button, select the directory to transfer from the page popped out. The numbers (1,2,3) or the items can be adjusted ( Figure 2). …”
Section: B Teaching Materials Management Modementioning
confidence: 99%
“…In the current industrial culture, vocational resource management includes teaching material classification and cultural environment support which is extracted from practice, required by the social demand of the profession [2,4,9]. In the management of network materials, the proposal of a new theory or practical problems is conducive to the construction of network platform and the enhancement of the innovative collection of theoretical and actual cases [1,3,20]. Class management, on-line and off-line teaching management, online examinations, assignments and marking management proposed in the Web Course Management System.…”
Section: Introductionmentioning
confidence: 99%